Reação de precipitação de Ag na liga Cu-8%Al-6%Ag - Silva, R. A.G. [UNESP]; Magdalena, A. G. [UNESP]; Carvalho, T. M. [UNESP] (Ecletica Quimica, 2008)
Ag precipitation reaction in the Cu-8wt.%Al-6wt.%Ag alloys was studied using microhardness measurements with temperature and ageing time, X-ray diffraction patterns (DRX), differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). The results obtained showed that the mechanism of Ag precipitation reaction is an Ag diffusion controlled process and reaction rate reaches a maximum at about 500ºC.
Ag precipitation reaction in the Cu-8%Al-6%Ag alloy
Keywords: Ag additions; Cu based alloys; Microhardness